Pengaruh Kualitas Pelayanan, Harga, dan Citra Merek terhadap Keputusan Pembelian Jasa Transportasi Online Maxim di Yogyakarta - Nadira Salsabilla; Wina Driyan Pradana (Journal of Management and Social Sciences, 2024)
Maxim is a Russian online transportation that has developed in Indonesia. The large number of online transportation in Indonesia makes Maxim offer affordable prices with many choices of services with good quality to attract customer. The study aims to determine the influence of service quality, price, and brand image on purchasing decisions for Maxim online transportation services. Using a quantitative approach, with data sources derived from primary and secondary data. Primary data was obtained by distributting questionnares to respondents. Secondary data sources were obtained from journals and books. The sample collection technique uses non-probability sampling (purposive sampling). The research sample was 168 respondents with the criteria of being students, residing in Yogyakarta, and had used Maxim,s online transportation services at least once. The data was processed using descriptive analysis test methods, instrument tests, classical assumption tests, multiple linear regression analysis, and hyphotesis testing with the help of SPSS 27 software. The result showed that serivec quality, price, and brand image influence purchasing decisions for Maxim online transportation services.